Wide clinical variability among 13 new Cockayne syndrome cases confirmed by biochemical assays. Issue 2 (20th January 2006) - Pasquier, L; Laugel, V; Lazaro, L; Dollfus, H; Journel, H; Edery, P; Goldenberg, A; Martin, D; Heron, D; Le Merrer, M; Rustin, P; Odent, S; et al.
Abstract : Cockayne syndrome is a multi-systemic, autosomal recessive disease characterised by postnatal growth failure and progressive multi-organ dysfunction. The main clinical features are severe dwarfism (<−2 SD), microcephaly (<−3 SD), psychomotor delay, sensorial loss (cataracts, pigmentary retinopathy, and deafness), and cutaneous photosensitivity. Here, 13 new cases of Cockayne syndrome are reported, which have been clinically diagnosed and confirmed using a biochemical transcription assay. The wide clinical variability, ranging from prenatal features to normal psychomotor development, is emphasised. When cardinal features are lacking, the diagnosis of Cockayne syndrome should be considered when presented with growth retardation, microcephaly, and one of the suggesting features such as enophthalmia, limb ataxia, abnormal auditory evoked responses, or increased ventricular size on cerebral imaging.